1991
DOI: 10.2307/3676592
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Fragmentation, Nest Site Selection, and Nest Predation Risk in Capercaillie

Abstract: Storch, I. 1990. Habitat fragmentation, nest site selection, and nest predation risk in Capercaillie. -Ornis Scand. 22: 213-217.Nest site preferences of Capercaillie Tetra° urogallus and nest predation risk in relation to habitat fragmentation patterns were studied in an area of the Bavarian Alps, West Germany. Nest sites were located through radio-equipped females. Hens strongly preferred to nest in edge habitats, namely between mature forests and clearcuts. Nest predation risk was assessed by an experiment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
2
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 18 publications
(15 reference statements)
5
33
2
1
Order By: Relevance
“…Artificial nests on track boards were used to obtain spatial replication and controlled stratification which would not have been possible using natural nests. This type of study design yields information about spatial and temporal prevalence of egg-consuming predators, thus indicating relative predation-risk patterns for ground-nesting birds (Angelstam 1986;Storch 1991;Villard and Pärt 2004;Manzer and Hannon 2005;McKinnon et al 2010). In each of the three study areas, we placed 12 transects (total of 36 transects) with three track boards (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Artificial nests on track boards were used to obtain spatial replication and controlled stratification which would not have been possible using natural nests. This type of study design yields information about spatial and temporal prevalence of egg-consuming predators, thus indicating relative predation-risk patterns for ground-nesting birds (Angelstam 1986;Storch 1991;Villard and Pärt 2004;Manzer and Hannon 2005;McKinnon et al 2010). In each of the three study areas, we placed 12 transects (total of 36 transects) with three track boards (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…On Teisenberg, capercaillie nests are typically placed at the edge between old forest and clearcuts where there is particularly good ground cover. An experiment with dummy nests showed that these may be the habitats with the lowest risk of nest predation (Storch, 1991). Records from Russia also show that capercaillie prefer to nest in edge habitats (Semenov-Tjan-Sanskij, 1960, cited in Klaus et al, 1986.…”
Section: Nesting Habitatmentioning
confidence: 99%
“…As chicks grow older, vegetative matter, and especially bilberry-the preferred food of adults-gains importance in the diet (SpidsO & Stuen, 1988;Storch et al, 1991). Bilberry supports higher arthropod densities than grass (Kastdalen & Wegge, 1985;Stuen & Spidsti, 1988;Biedermann, 1992) and thus provides both optimal plant and animal food for chicks.…”
Section: Habitat and Range Use By Broodsmentioning
confidence: 99%
See 2 more Smart Citations